2017
DOI: 10.18632/oncotarget.17090
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of nivolumab combined with IFN-β for patients with advanced melanoma

Abstract: The efficacy of nivolumab is greater than that of other anti-melanoma drugs, so nivolumab-based combined therapies that enhance anti-tumor immune responses in patients with metastatic melanoma are of great interest to dermato-oncologists. As we have previously reported, IFN-β enhances the anti-tumor immune response of anti-PD-1 antibodies against B16F10 melanoma in vivo. To explore the potential of this property of IFN-β as part of a combination therapy for the treatment of metastatic melanoma patients, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Nevertheless, our data suggest that the next-generation PD-L1 antibody armed with IFNα can overcome tumor resistance to checkpoint blockade therapy in advanced tumors. The combination therapy of type I IFN with PD-1 blockade Ab for patients with advanced melanoma tested in phase I study have demonstrated the safety, and several other clinical trials are ongoing 34 . Our strategy of constructing IFNα-anti-PD-L1 may be important for improving current immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data suggest that the next-generation PD-L1 antibody armed with IFNα can overcome tumor resistance to checkpoint blockade therapy in advanced tumors. The combination therapy of type I IFN with PD-1 blockade Ab for patients with advanced melanoma tested in phase I study have demonstrated the safety, and several other clinical trials are ongoing 34 . Our strategy of constructing IFNα-anti-PD-L1 may be important for improving current immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TAMs are a heterogeneous population of cells that could be polarized to M1-like macrophages in the tumor microenvironment (21). Therefore, TAMs could be a promising immunotherapy target in the treatment of melanoma (13,28).…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab can mediate tumor regression by binding to and blocking the activation of PD‐1, and these responses are durable and persisted after drug discontinuation . It has been reported that IFN‐β enhances the antitumor immune response of anti‐PD‐1 antibodies against melanoma cells in vivo and a phase I study of nivolumab combined with IFN‐β for patients with advanced melanoma has been performed . In our case, DAV‐feron therapy provided antitumor effects on an invasive tumor on the upper gingiva, but not black macular lesions on the hard palate.…”
Section: Discussionmentioning
confidence: 61%